Beginning Korean 1 - Yoon, Sang-Seok (Open textbook library., 2022)
The Beginning Korean 1 is designed for elementary Korean learners to practice and learn how to communicate in Korean. It provides basic grammar, vocabulary, and discourse information that are essential to beginning level students. This book is ideal for learners at the Novice Low to Novice High levels who want to practice writing and pronouncing hangeul, communicate in Korean by creating sentences using basic grammar and vocabulary, and understand and create simple conversations that are useful in everyday conversations